Women in Livy: performativity and historiographical conventions - Haywood, Bethany Paige (2025)
This thesis examines three social roles occupied by women in Livy – those of daughters, wives, and mothers. The final chapter, ‘Others’, considers the intersection between gender and ethnicity by examining Livy’s presentation of ‘non-Roman’ female protagonists. This thesis will demonstrate that Livy’s character types revolve around androcentric expectations for female familial roles and Romano-centric stereotypes for certain ethnic groups that were considered outsiders. This thesis argues that Livy uses a series of linguistic and narrative frameworks to perpetuate female character types. These character types are not Livian inventions: they are a combination of social expectations and pre-established female characterisation not only from historiography, but gynocentric stock characters from the genres of tragedy and comedy. Livy unpicks and deconstructs these characters in episodes that contain tragic motifs, dramatic stagecraft, and performance. This thesis explores Livy’s appropriation of female characters through a male lens and argues for the complex and often transgressive characterisation of female protagonists as told through a series of tragic performances. There is currently no comprehensive analysis of the intersection between women, drama, and performance in Livy. In previous scholarly research these topics have been analysed separately with a focus on select protagonists from the first pentad. This thesis is the first to consider female character types and performativity through an extensive study of Livy’s narrative strategies, with a focus on intratextuality between the first pentad (books 1-5) and the third and fourth decades (books 21-45).